Innovation, commercialization, and start-ups in life sciences - Jordan, James F. (CRC Press, 2015)
"This book specifically provides the reader with the methodologies necessary to create a successful life sciences start-up from initiation to exit. The readers gain an appreciation for the necessary data, partnership, and skills to be acquired and the constituencies that must be satisfied, along the way. It presents data and analytical processes articulating the fundable milestones for angel and venture capital. It also provides tools for creating branding for public investors and more"...Provided by publisher
Includes bibliographical references (pages 219-224) and index
Keywords: Biotechnology industries; New business enterprises; Biological Science Disciplines; Entrepreneurship; Commerce; Investments; Small Business; Biowissenschaften; Due Diligence; Innovation; Unternehmensgründung